# Trigonometric Equations

Covid-19 has led the world to go through a phenomenal transition .

E-learning is the future today.

Stay Home , Stay Safe and keep learning!!!

In this section we will discuss trigonometric equations.
An equation involving trigonometric ratios of an angle θ (say) is said to be a trigonometric equations, if it is satisfied for all values of θ for which the given trigonometric ratios are defined.
Some Trigonometric-equations (Identities) are as follows :

 1) sin2θ + cos2θ= 1 2) sin2θ = 1 - cos2θ 3) cos2θ = 1 - sin 2θ 4) 1 + tan2θ = sec2θ 5) tan2θ = sec2θ - 1 6) sec2θ - tan2θ = 1 7) 1 + cot2θ = csc2θ 8) cot2θ = csc2θ - 1 9) csc2θ - cot2θ = 1 10) sec θ + tan θ = 1 / ( sec θ - tan θ) 11) csc θ + cot θ = 1 / ( csc θ - cot θ)

These Trigonometric equations are true for any angle θ for which the trigonometric ratios are meaningful.

Some Solved Examples on Trigonometric Equations :

1) 1 / (1 + sin θ) + 1 / ( 1 – sin θ ) = 2 sec2θ

Solution :
Consider 1 / (1 + sin θ) + 1 / ( 1 – sin θ )
LCM = (1 + sin θ)( 1 – sin θ )
= [1 (1 – sin θ) + 1 ( 1 + sin θ )] / (1 + sin θ)( 1 – sin θ)
= ( 1 – sin θ + 1 + sin θ ) / (1 + sin θ)( 1 – sin θ )
= 2 / (1 – sin2θ ) [ use identity (a + b) ( a – b ) = a2 - b2]
= 2 / cos2θ
= 2 sec2θ
∴ 1 / (1 + sin θ) + 1 / ( 1 – sin θ ) = 2 sec2θ
________________________________________________________________
2) Prove that : cos θ / ( 1- sin θ ) = ( 1 + sin θ) / cos θ

Solution :
Consider cos θ / ( 1- sin θ )
Multiply top (numerator) and bottom(denominator) by 1 + sin θ
= cos θ( 1 + sin θ) / ( 1- sin θ )( 1 + sin θ)
= cos θ ( 1 + sin θ) / ( 1- sin2θ )
[ using this identity (a + b)(a – b ) = a2- b2]
= cos θ ( 1 + sin θ) / cos2θ )
= (1 + sin θ) / cos θ
∴ cos θ / ( 1- sin θ ) = ( 1 + sin θ) / cos θ
________________________________________________________________
3) Cos2 θ + 1 / ( 1 + cot2 θ ) = 1

Solution :
Consider Cos2 θ + 1 / ( 1 + cot2 θ )
= Cos2 θ + 1/ csc2 θ [ since 1 + cot2θ = csc2θ]
= cos2θ + sin2θ [ since 1/ csc2 θ = sin2θ ]
= 1 [ since sin2θ + cos2θ= 1 ]
∴ Cos2 θ + 1 / ( 1 + cot2 θ ) = 1

Trigonometry

SOHCAHTOA -Introduction to Trigonometry
Trigonometric ratios and their Relation
Trigonometry for specific angles
Complementary angles in Trigonometry
Trigonometric Equations